1980
DOI: 10.1088/0022-3727/13/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target purity on laser-produced plasma expansion

Abstract: The effects of target surface impurities on the laser-produced plasma were studied by means of Thomson ion spectrograms and time-of-flight measurements of the plasma ions. Hydrocarbons were believed to be the most likely surface impurity. Consequently, polyethylene was used to characterise an impure target. For comparison, pure targets (5 to 20 ppm impurities) of C, Ti, and Ta and a standard quality Ti target were used. The fastest Cz+ ions from the plasma expansion using a polyethylene target had the same pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is known that the complete charge-state spectrum of ions can be recorded far from the irradiated target even though the plasma temperature is so high that light elements should be fully ionized [1,5]. Moreover, recent experiments have shown that the expanding plasmas of medium and heavy elements consist of multiply charged as well as highly charged ions [6].…”
Section: Tof Analysismentioning
confidence: 99%
“…It is known that the complete charge-state spectrum of ions can be recorded far from the irradiated target even though the plasma temperature is so high that light elements should be fully ionized [1,5]. Moreover, recent experiments have shown that the expanding plasmas of medium and heavy elements consist of multiply charged as well as highly charged ions [6].…”
Section: Tof Analysismentioning
confidence: 99%
“…As already mentioned, the intensity of the target ions is also sensitive to the surface contamination [1,19]. At a vacuum pressure of the order of 10 −6 mbar, the surfaces are known to be covered with a thin layer of adsorbates [28,29]. In accord ance with the kinetic theory of gases, the impingement rate of the residual gas atoms on a surface is given as…”
Section: Resultsmentioning
confidence: 98%